Clinical indications for cesarean delivery among women living with female genital mutilation. Issue 1 (20th July 2017) - Rodriguez, Maria I.; Say, Lale; Abdulcadir, Jasmine; Hindin, Michelle J.
Abstract: Objective: To compare primary indications for cesarean delivery among patients with different female genital mutilation (FGM) status. Methods: The present secondary analysis included data from women who underwent trial of labor resulting in cesarean delivery at 28 obstetric centers in six African countries between November 1, 2001, and March 31, 2003. Associations between cesarean delivery indications and FGM status were assessed using descriptive statistics and multivariable multinomial logistic regression. Results: Data from 1659 women (480 patients with no type of FGM and 1179 patients with FGM [any type]) were included; cesarean delivery indications were collapsed into five categories (fetal indications, maternal factors, stage 1 arrest, stage 2 arrest, and other). The incidence of a clear medical indication for cesarean delivery did not differ between the groups ( P =0.320). Among patients without a clear indication for cesarean delivery, women with FGM were more likely to have undergone cesarean delivery for maternal factors (adjusted relative risk ratio [aRRR] 3.92, 95% confidence interval [CI] 1.3–11.71), stage 1 arrest (aRRR 7.74, 95% CI 1.33–45.07), stage 2 arrest (aRRR 6.63, 95% CI 3.74–11.73), or other factors (aRRR 2.41, 95% CI 1.04–5.60) rather than fetal factors compared with women who had no type of FGM. Conclusion: Among women with unclear medical indications, FGM was associated with cesarean delivery being performed for maternal factors or arrest disorders. Abstract : Women living with FGM were more likely to have maternal factors of arrest disorders contribute to undergoing a cesarean delivery for an unclear medical indication.